Zero Trust Architecture as a New Paradigm in Cyber Security - Andi M. Yusuf; Dian Megah Sari; Hilda Ashari; Hamdy Nur Saidy; Musawwir (Journal of Embedded Systems, Security and Intelligent Systems, 2025)
The traditional perimeter-based security model has proven inadequate in addressing modern cybersecurity challenges characterized by cloud adoption, remote work, and sophisticated cyber threats. This mixed-methods study examines Zero Trust Architecture (ZTA) as an emerging paradigm that fundamentally shifts security principles from "trust but verify" to "never trust, always verify." Through systematic literature review of 156 peer-reviewed articles and analysis of 12 cross-sector implementation case studies, this research explores the core principles, implementation strategies, benefits, and challenges of ZTA adoption. Key quantitative findings demonstrate that organizations implementing ZTA achieve 67% reduction in breach costs, 48% improvement in threat detection, and 52% enhancement in incident response capabilities. However, implementation faces significant barriers including technical complexity (78% of organizations), cultural resistance (65%), and skills gaps (72%). This study contributes a novel cross-sector ZTA maturity framework and provides evidence-based insights for cybersecurity professionals and organizational leaders considering ZTA adoption.